KARAKTERISTIK TIPE PAKAN KELELAWAR PEMAKAN BUAH DAN NEKTAR DI DAERAH PERKOTAAN: STUDI KASUS DI KEBUN RAYA BOGOR - Soegiharto, Sri; Kartono, Agus P. (JURNAL BIOLOGI INDONESIA, 2009)
ABSTRACTFood TypeCharacteristic of the Fruit Bats at Urban Area: A Case Study in Bogor BotanicalGarden, West Jawa. Bats have important role on seed dispersal and or plant pollinator. Theidentification of flower and their pollens as the feed resource for bats was conducted in BogorBotanical Gargen. The resultsof this study showed that Eonycteris spelaea male has interestsin with personatus corola type flower, while the female in disk type. Furthermore the male ofMacroglossus sobrinus has interested in rotatus, tubulosus, and perferesence, corola types.Where as the female has interest in campanulatus type. The campanulatus and papilionaceustypes has a potential to be visitd by Cynopterus minutus male and female of C. sphinx;Urceolatus type has important for female of C. titthaheileus and C. brachyotis. The male ofMacroglossus sobrinus and female of Eonycteris spelaea has interests to visit the flower withsuboblate and prolate spheroidal pollen types; prolate pollen type has importance for themale of Eonycteris spelaea; oblate type for the male of C. minutus, C. brachyotis and C.titthaheileus; oblate spheroidal for the female of Rousettus amplexicaudatus and male of C.sphinx. The male of C. titthaheileus and female of Macroglossus sobrinus has interests ingigantic type (>200 ì m), while the female of C. sphinx, C. brachyotis and R. amplexicaudatuslike permagnae type (100-200 ì m).Key words: Fruit bats, pollen identification, urban areaKata kunci: Kelelawar buah, pollen, identifikasi, perkotaan